RETRACTED: Molecular Cloning and Docking of speB Gene Encoding Cysteine Protease With Antibiotic Interaction in Streptococcus pyogenes NBMKU12 From the Clinical Isolates - Balasubramanian, Natesan; Varatharaju, Govintharaj; Shanmugaiah, Vellasamy; Balakrishnan, Karuppiah; Thirunarayan, Mandayam A. (Frontiers in Microbiology, 2018)
Streptococcus pyogenes cause a wide variety of infections from mild diseases to severe invasive infections as a result significant morbidity and mortality. Therefore, this study focuses on S. pyogenes to elucidate antibiotic resistance and their interaction with cysteine protease. Among 36 beta-hemolytic isolates collected from the clinical lab, seven isolates (19.4%) were identified as Streptococcus pyogenes. Among them, one of the isolate was collected from urinary tract infection, which was identified by antibody agglutination and MALTI-TOF-MS, and it is designated as S. pyogenes NBMKU12. An 8.3 to 66.6 % of their isolates were resistant to one or more antimicrobial agents, particularly, 29.1% were penicillin-G resistance. In the NBMKU12 isolate, the beta lactem (TEM) gene was detected among the 13 antibiotic genes tested. Furthermore, 13 virulence genes searched in NBMKU12 isolate, only speJ and speB were detected. The speB (streptococcal pyrogenic exotoxin B) encoding cysteine protease gene was cloned and DNA sequencing was performed to understand the putative cysteine protease interaction with antibiotics, inhibitors and substrate. The speB gene consists of 1197 nucleotides which encodes a protein with multiple domains, including a signal peptide (aa 1–22), an inhibitor region (aa 27–156), and a catalytic cysteine domain (aa 160–367). The signal peptide cleavage site is predicted between Ala22 and Asn23. The putative 398 amino acid residues calculated theoretical pI is 8.76 with a molecular mass of 43,204.36 Da. The culture supernatants of tested NBMKU12 isolate showed proteolytic activity against casein, papaya and pineapple substrates and it suggests that speB gene expression. Molecular docking analysis of cysteine protease showed erythromycin (bond length 2.41 Å) followed by chloramphenicol (2.51 Å) had strong interaction; whereas penicillin-G (3.24 Å) had weak interaction, this might be a cause for penicillin-G resistance. The present study contributes to a better understanding of speB gene encoding cysteine protease, antibiotic resistance and their interaction in the isolate, S. pyogenes NBMKU12. The antibiotics and cysteine protease interaction study confirms the resistance or sensitivity of S. pyogenes. Hence, it could be hypothesized that, the isolate NBMKU12 is resistance to most of the tested antibiotics and this resistance might be a cause of mutation.